2021
DOI: 10.13189/ujaf.2021.090418
|View full text |Cite
|
Sign up to set email alerts
|

Making Environmental Accounting Work: Case of the Zimbabwe Mining Industry

Abstract: The research sought to find out how environmental accounting can work in Zimbabwean Mining Companies. Descriptive research design was used and mixture of qualitative and quantitative data was collected using questionnaires and interviews. Stratified purposeful sampling of 52 respondents was made up of 16 Mining Companies' executives which are dominant companies in mining gold, nickel, asbestos, coal, copper and chromite, 20 government organisations representatives and 16 mining communities' heads (8 Chiefs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“…The process of descriptive analysis entails transforming raw data into an easily understandable and interpretable format, that is, rearranging, organizing and transforming the data to provide meaningful information about the available data set (Olubukola et al , 2021). Figure 4 illustrates the top nine most influential nations based on the number of tweets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of descriptive analysis entails transforming raw data into an easily understandable and interpretable format, that is, rearranging, organizing and transforming the data to provide meaningful information about the available data set (Olubukola et al , 2021). Figure 4 illustrates the top nine most influential nations based on the number of tweets.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, research on the causal link between corporate performance and green accounting is ambiguous. Studies have shown that the relationship is favorable (Lusiana et al , 2021; Magara et al , 2015; Olubukola et al , 2021). However, other studies have shown that green accounting negatively impacts a company’s overall financial health (Adediran and Alade, 2013; Huseno, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The Iraq's environmental activities was examined by Al-waeli, et al (2021 & 2020) [9][10] . In Zimbabwe, Olubukola, et al (2021) [47] , examines the level of environmental protection. Kaspersen (2013) [35] , carried out his study in Denmark.…”
Section: Empirical Review and Hypotheses Developmentmentioning
confidence: 99%
“…Cómo hacer que la contabilidad ambiental funcione: El caso de la industria minera (Olubukola et al, 2021), mencionan que el el gobierno no está haciendo lo suficiente para fomentar la aplicación de la contabilidad medioambiental; el sector minero se ha politizado, lo que dificulta la aplicación de las leyes medioambientales en este sector, mientras que, por otro lado, no hay leyes ni políticas eficaces que regulen las cuestiones de contabilidad medioambiental. Los núcleos de inestabilidad económica y agitación política en la nación han obligado a las empresas a concentrarse en su existencia económica continuada, sin hacer casi nada en materia de contabilidad medioambiental.…”
Section: Categoría 3: Enfoque Críticounclassified